Synthesis, Characterization, Crystal Structure and Free Radical Scavenging Activities of 2-(2-Butylamine)-6-[(2-butylamine)amino]-5-nitro-1H-benzo[de]-isoquinoline-1,3(2H)-dione - Tang, Xiaolin; Zhang, Ye; Qin, Wen; Liao, Yongzhi (Asian Journal of Chemistry, 2014)
2-(2-Butylamine)-6-[(2-butylamine)amino]-5-nitro-1H-benzo[de]-isoquinoline-1,3(2H)-dione (2) was synthesized and then characterized by FT-IR, NMR and elemental analysis. The crystal structure of compound 2 was investigated using X-ray diffraction and SHELXTL97 software and the result indicated that compound 2 crystallized in the monoclinic system, space group C2/c with a = 32.1094 (19), b = 7.1888 (4), c = 16.7750 (9) Å, V = 3827.2 (4) Å3; Z = 8. The free radical scavenging activity screening results showed that compound 2 exhibited good scavenging activity against 2,2-diphenyl-1-picrylhydrazyl radical (DPPH•), with IC50 of 214.7 μM.